Lithium cobalt oxide positive electrode material and preparation method thereof, positive plate and battery

By adopting the combined Class I and Class II cobalt oxide positive electrode materials, the wide particle size distribution and conventional particle size distribution are used to solve the problems of low energy density and poor stability at high voltages, high energy density and long-term stability are achieved, and the cycle life and safety performance of lithium-ion batteries are improved.

CN119650654APending Publication Date: 2025-03-18TIANJIN B&M SCI & TECH LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411872031.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Lithium cobalt oxide cathode material has problems of low energy density and poor stability at high voltages, which affects the cycle life and safety performance of the battery.

Method used

The combination of Class I and Class II positive electrode materials is adopted, with a wide particle size distribution and a conventional particle size distribution respectively. Through specific doping elements and calcining processes, the compaction density and particle distribution of the material are improved, thereby improving energy density and cycling stability.

Benefits of technology

It achieves high energy density and long-term stability at high voltages, improving the cycle life and safety performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005196001250000141
    Figure BDA0005196001250000141
  • Figure BDA0005196001250000151
    Figure BDA0005196001250000151
  • Figure HDA0005196001260000011
    Figure HDA0005196001260000011
Patent Text Reader

Abstract

The invention provides a lithium cobalt oxide positive electrode material and a preparation method thereof, a positive plate and a battery. According to the lithium cobalt oxide positive electrode material with high compaction density provided by the invention, a finished product with a large number of medium-particle-size particles is obtained through two positive electrode materials with different particle sizes, and the particles can be better distributed, so that the purposes of improving the energy density and prolonging the cycle life under high voltage are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium cobalt oxide positive electrode material and a preparation method thereof, a positive electrode sheet, and a battery. Background Art

[0002] As one of the greatest inventions of the 20th century, lithium-ion batteries are widely used in all aspects of human life due to their advantages such as high specific energy, long cycle life, no memory effect and low self-discharge rate. The positive electrode material is the core component of lithium-ion batteries, among which lithium cobalt oxide positive electrode material is widely used in lithium-ion battery positive electrode materials because of its high theoretical capacity, good rate performance and high volume energy density.

[0003] However, the charging cut-off voltage of lithium cobalt oxide positive electrode materials in actual applications is lower than 4.45V, and the capacity is lower than 173mAh / g. The actual application capacity of lithium cobalt oxide positive electrode materials is far lower than the theoretical value. In order to further increase the specific capacity of lithium cobalt oxide and improve the energy density of the battery, it is necessary to increase the charging cut-off voltage of lithium cobalt oxide batteries. However, under high voltage, the material will gradually experience irreversible structural phase changes, side reactions on the surface interface, and reduced safety performance. Therefore, maintaining the long-term stability of materials under high voltage is a technical focus that lithium cobalt oxide batteries need to overcome. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a lithium cobalt oxide positive electrode material and a preparation method thereof, a positive electrode sheet, and a battery. The lithium cobalt oxide positive electrode material provided by the present invention has excellent energy density and long-term stability under high voltage.

[0005] The present invention provides a lithium cobalt oxide positive electrode material, including type I positive electrode material and type II positive electrode material;

[0006] The chemical formula of the type I positive electrode material is Li u Co 1-x A x O2; wherein 1.05<u≤1.07, 0≤x<1, A comprises at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, zirconium, niobium, indium, fluorine, chlorine, and sulfur;

[0007] The chemical formula of the type II positive electrode material is Li v Co 1-y M y O2; wherein 1.05<v≤1.07, 0≤y<1, and M comprises at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, strontium, germanium, niobium, indium, zirconium, fluorine, chlorine, and sulfur;

[0008] The median particle size D of the type I positive electrode material 50(Ⅰ)The median particle size D of the type II positive electrode material is 16.5 μm to 20.5 μm. 50(Ⅱ) 4.0μm~6.5μm;

[0009] The mass ratio of the type I positive electrode material to the type II positive electrode material is 3 to 5:1;

[0010] The compaction density of the lithium cobalt oxide positive electrode material is 4.04-4.18 g / cm 3 .

[0011] Preferably, the type I positive electrode material is prepared from a precursor material having a wide particle size distribution;

[0012] The type II positive electrode material is prepared from a precursor material having a conventional particle size distribution;

[0013] The wide particle size distribution precursor material has a diameter distance of 0.80 to 1.00 and a median particle size of 15 to 18 μm;

[0014] The conventional particle size distribution of the precursor material has a diameter distance of 0.2 to 0.3 μm and a median particle size of 2.5 to 6 μm.

[0015] Preferably, the wide particle size distribution precursor material is a doped cobalt-containing precursor material, the cobalt-containing precursor is selected from one or more of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt carbonate, cobalt oxalate and cobalt oxyhydroxide, the doping element is one or more of aluminum, magnesium, nickel, manganese, titanium and zirconium, and the doping amount of the doping element is 6000-9000 ppm;

[0016] The conventional particle size distribution precursor material is a doped cobalt-containing precursor material, the cobalt-containing precursor is selected from one or more of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt carbonate, cobalt oxalate and cobalt oxyhydroxy, the doping element is one or more of aluminum, magnesium, nickel, manganese, titanium and zirconium, and the doping amount of the doping element is 6000 to 11000 ppm.

[0017] Preferably, the raw materials for preparing the lithium cobalt oxide positive electrode material also include a coating material, the coating material includes a cobalt source compound and a compound containing a coating element, the coating element is at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, strontium, germanium, niobium, indium, zirconium, lanthanum and halogen elements; the cobalt source compound is selected from one or more of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, nano cobalt carbonate and cobalt oxyhydroxyl;

[0018] The cobalt source compound accounts for 0.25% to 0.75% of the total mass of the type I positive electrode material and the type II positive electrode material;

[0019] The compound containing the coating element accounts for 500 to 3000 ppm of the total mass of the type I positive electrode material and the type II positive electrode material.

[0020] Preferably, the specific surface area of ​​the lithium cobalt oxide positive electrode material is 0.14-0.24m 2 / g, tap density is 2.8-3.2g / cm 3 .

[0021] The present invention also provides a method for preparing a lithium cobalt oxide positive electrode material, comprising the following steps:

[0022] The type I positive electrode material, the type II positive electrode material and the coating material are mixed and calcined to obtain a lithium cobalt oxide positive electrode material.

[0023] Preferably, the calcination is: raising the temperature to 700°C to 900°C at a heating rate of 2 to 4°C / min, and keeping the temperature for 5 to 8 hours;

[0024] The calcination atmosphere is air, oxygen or nitrogen.

[0025] Preferably, the method for preparing the Class I positive electrode material comprises:

[0026] The wide particle size distribution precursor, the lithium source and the compound containing the A element are uniformly mixed, calcined and crushed to obtain a type I positive electrode material;

[0027] The preparation method of the type II positive electrode material comprises:

[0028] The conventional particle size distribution precursor, the lithium source and the compound containing the M element are uniformly mixed, calcined and crushed to obtain the type II positive electrode material;

[0029] Preferably, the lithium source used to prepare the type I positive electrode material and the type II positive electrode material is independently selected from one or more of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide and lithium fluoride;

[0030] Preferably, the calcination in the process of preparing the Class I positive electrode material comprises two stages, the first stage is to increase the temperature to 600°C to 800°C at a heating rate of 3 to 8°C / min and keep it warm for 2 to 4 hours, and the second stage is to increase the temperature to 1050°C to 1100°C at a heating rate of 1 to 3°C / min and keep it warm for 5 to 8 hours;

[0031] The calcination process in the preparation of the Class II positive electrode material includes two stages. The first stage is to increase the temperature to 600°C to 800°C at a heating rate of 3 to 8°C / min and keep it warm for 2 to 4 hours. The second stage is to increase the temperature to 980°C to 1015°C at a heating rate of 1 to 3°C / min and keep it warm for 5 to 8 hours.

[0032] The present invention also provides a positive electrode plate, comprising the above-mentioned lithium cobalt oxide positive electrode material.

[0033] The present invention also provides a lithium-ion battery, comprising the above-mentioned positive electrode plate.

[0034] Compared with the prior art, the present invention provides a lithium cobalt oxide positive electrode material, including type I positive electrode material and type II positive electrode material; the chemical formula of the type I positive electrode material is Li u Co 1-x A x O2; wherein 1.05<u≤1.07, 0≤x<1, A includes at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, zirconium, niobium, indium, fluorine, chlorine, and sulfur; the chemical formula of the type II positive electrode material is Li v Co 1-y M y O2; wherein 1.05<v≤1.07, 0≤y<1, the M comprises at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, strontium, germanium, niobium, indium, zirconium, fluorine, chlorine, and sulfur; the median particle size D of the Class I positive electrode material 50(Ⅰ) The median particle size D of the type II positive electrode material is 16.5 μm to 20.5 μm. 50(Ⅱ) The density of the lithium cobalt oxide positive electrode material is 4.0 μm to 6.5 μm; the mass ratio of the type I positive electrode material to the type II positive electrode material is 3 to 5:1; and the compaction density of the lithium cobalt oxide positive electrode material is 4.04 to 4.18. The lithium cobalt oxide positive electrode material with high compaction density provided by the present invention obtains a finished product with a large number of medium-sized particles by using two positive electrode materials with different particle sizes, which can make the particles better distributed, thereby achieving the purpose of improving energy density and cycle life under high voltage. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM image of the precursor material with conventional particle size distribution in Example 1;

[0036] Figure 2 This is a SEM image of the precursor material with a wide particle size distribution in Example 1;

[0037] Figure 3 The particle size distribution diagram of the conventional particle size distribution precursor material and the wide particle size distribution precursor material in Example 1;

[0038] Figure 4 The particle size distribution diagram of the type I positive electrode material in Example 1 and Comparative Example 1;

[0039] Figure 5 The particle size distribution diagram of the lithium cobalt oxide positive electrode material in Examples 1 to 6 and Comparative Example 1;

[0040] Figure 6The SEM images of the lithium cobalt oxide positive electrode materials in Example 1 and Comparative Example 1;

[0041] Figure 7 is the compaction density of the lithium cobalt oxide positive electrode material in Example 1 and Comparative Example 1;

[0042] Figure 8 The first charge and discharge curves of the batteries obtained from the lithium cobalt oxide positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 respectively;

[0043] Fig. 9 The cycle performances of the batteries obtained from the lithium cobalt oxide positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 respectively. DETAILED DESCRIPTION

[0044] The present invention provides a lithium cobalt oxide positive electrode material, including type I positive electrode material and type II positive electrode material;

[0045] The chemical formula of the type I positive electrode material is Li u Co 1-x A x O2; wherein 1.05<u≤1.07, 0≤x<1, A comprises at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, zirconium, niobium, indium, fluorine, chlorine, and sulfur;

[0046] The chemical formula of the type II positive electrode material is Li v Co 1-y M y O2; wherein 1.05<v≤1.07, 0≤y<1, and M comprises at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, strontium, germanium, niobium, indium, zirconium, fluorine, chlorine, and sulfur;

[0047] The median particle size D of the type I positive electrode material 50(Ⅰ) The median particle size D of the type II positive electrode material is 16.5 μm to 20.5 μm. 50(Ⅱ) 4.0μm~6.5μm;

[0048] The mass ratio of the type I positive electrode material to the type II positive electrode material is 3 to 5:1;

[0049] The compaction density of the lithium cobalt oxide positive electrode material is 4.04-4.18.

[0050] In the present invention, the chemical formula of the type I positive electrode material is Li u Co 1-x A x O2; wherein 1.05<u≤1.07, 0≤x<1, A includes at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, zirconium, fluorine, chlorine, and sulfur, and the median particle size D of the Class I positive electrode material 50(Ⅰ)16.5μm~20.5μm;

[0051] The type I positive electrode material is prepared from a precursor material with a wide particle size distribution. The diameter of the precursor material with a wide particle size distribution is 0.80 to 1.00, which can be 0.80, 0.85, 0.90, 0.95, 1.00, or any value between 0.80 and 1.00; the median particle size is 15 to 18 μm, which can be 15, 16, 17, 18, or any value between 15 and 18 μm.

[0052] In the present invention, the diameter distance is calculated by the formula shown in Formula I:

[0053] Diameter distance = (D90-D10) / D50) Formula I

[0054] In formula I, D10: the particle size corresponding to when the cumulative distribution accounts for 10% in the system;

[0055] D50: The particle size corresponding to when the cumulative distribution in the system accounts for 50%;

[0056] D90: The particle size corresponding to when the cumulative distribution in the system accounts for 90%.

[0057] The wide particle size distribution precursor material is a doped cobalt-containing precursor material, the cobalt-containing precursor is selected from one or more of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt carbonate, cobalt oxalate and cobalt oxyhydroxy, the doping element is one or more of aluminum, magnesium, nickel, manganese, titanium and zirconium, the doping amount of the doping element is 6000-9000 ppm, and can be 6000, 6500, 7000, 7500, 8000, 8500, 9000, or any value between 6000 and 9000 ppm.

[0058] In the present invention, the method for preparing the Class I positive electrode material preferably comprises the following steps:

[0059] The wide particle size distribution precursor, the lithium source and the compound containing the A element are uniformly mixed, calcined and crushed to obtain a type I positive electrode material;

[0060] Wherein, the lithium source is selected from one or more of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide and lithium fluoride;

[0061] In the compound containing element A, A includes at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, zirconium, niobium, indium, fluorine, chlorine, and sulfur;

[0062] The molar ratio of lithium in the lithium source to cobalt in the wide particle size distribution precursor is (1.05-1.08):1, and can be 1.05:1, 1.06:1, 1.07:1, 1.08:1, or any value between (1.05-1.08):1.

[0063] The calcination process in the preparation of the Class I cathode material includes two stages:

[0064] The first stage is to increase the temperature to 600°C-800°C at a heating rate of 3-8°C / min and keep it warm for 2-4h; wherein the heating rate can be 3, 4, 5, 6, 7, 8, or any value between 3-8°C / min, the roasting temperature can be 600, 650, 700, 750, 800, or any value between 600°C-800°C, and the keeping time can be 2, 2.5, 3, 3.5, 4, or any value between 2-4h.

[0065] The second stage is to increase the temperature to 1050°C~1100°C at a heating rate of 1~3°C / min and keep it warm for 5~8h; wherein, the heating rate can be 1, 1.5, 2, 2.5, 3, or any value between 1~3°C / min, the roasting temperature can be 1050, 1060, 1070, 1080, 1090, 1100, or any value between 1050°C~1100°C, and the insulation time can be 5, 6, 7, 8, or any value between 5~8h.

[0066] In the present invention, the calcination atmosphere is air, oxygen or nitrogen.

[0067] The chemical formula of the type II positive electrode material is Li v Co 1-y M y O2; wherein 1.05<v≤1.07, 0≤y<1, the M comprises at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, strontium, germanium, niobium, indium, zirconium, fluorine, chlorine, and sulfur; the median particle size D of the Class II positive electrode material 50(Ⅱ) It is 4.0 μm to 6.5 μm, and can be 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, or any value between 4.0 μm and 6.5 μm.

[0068] The Class II positive electrode material is prepared from a precursor material with a conventional particle size distribution, the diameter of the precursor material with a conventional particle size distribution is 0.2 to 0.3, which can be 0.2, 0.22, 0.24, 0.25, 0.26, 0.28, 0.30, or any value between 0.2 and 0.3, and the median particle size is 2.5 to 6 μm, which can be 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, or any value between 2.5 and 6 μm.

[0069] Among them, the conventional particle size distribution precursor material is a doped cobalt-containing precursor material, the cobalt-containing precursor is selected from one or more of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt carbonate, cobalt oxalate and cobalt oxyhydroxy, the doping element is one or more of aluminum, magnesium, nickel, manganese, titanium and zirconium, and the doping amount of the doping element is 6000 to 11000 ppm, which can be 6000, 7000, 8000, 9000, 10000, 11000, or any value between 6000 and 11000 ppm.

[0070] The preparation method of the type II positive electrode material comprises:

[0071] The conventional particle size distribution precursor, lithium source and compound containing M element are uniformly mixed, roasted and crushed to obtain type II positive electrode material.

[0072] Wherein, the lithium source is selected from one or more of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide and lithium fluoride;

[0073] In the compound containing the element M, M includes at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, zirconium, fluorine, chlorine, and sulfur;

[0074] The molar ratio of lithium in the lithium source to cobalt in the wide particle size distribution precursor is (1.05-1.08):1, and can be 1.05:1, 1.06:1, 1.07:1, 1.08:1, or any value between (1.05-1.08):1.

[0075] The calcination process in the preparation of the Class II cathode material includes two stages:

[0076] The first stage is to increase the temperature to 600°C-800°C at a heating rate of 3-8°C / min and keep it warm for 2-4h; wherein the heating rate can be 3, 4, 5, 6, 7, 8, or any value between 3-8°C / min, the roasting temperature can be 600, 650, 700, 750, 800, or any value between 600°C-800°C, and the keeping time can be 2, 2.5, 3, 3.5, 4, or any value between 2-4h.

[0077] The second stage is to increase the temperature to 980°C~1015°C at a heating rate of 1~3°C / min and keep it warm for 5~8h; wherein, the heating rate can be 1, 1.5, 2, 2.5, 3, or any value between 1~3°C / min, the roasting temperature can be 980, 990, 1000, 1010, 1015, or any value between 980°C~1015°C, and the insulation time can be 5, 6, 7, 8, or any value between 5~8h.

[0078] In the present invention, the calcination atmosphere is air, oxygen or nitrogen.

[0079] In the present invention, the mass ratio of the type I positive electrode material to the type II positive electrode material is 3 to 5:1, and can be 3:1, 3.5:1, 4:1, 4.5:1, 5:1, or any value between 3 and 5:1.

[0080] In some preferred embodiments of the present invention, the raw materials for preparing the positive electrode material further include a coating material, the coating material includes a cobalt source compound and a compound containing a coating element, the coating element is at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, strontium, germanium, niobium, indium, zirconium and halogen elements; the cobalt source compound is selected from one or more of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, nano cobalt carbonate and cobalt oxyhydroxyl;

[0081] The cobalt source compound accounts for 0.25% to 0.75% of the total amount of the Class I positive electrode material and the Class II positive electrode material, and can be 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, or any value between 0.25% and 0.75%;

[0082] The compound containing the coating element accounts for 500 to 3000 ppm of the total amount of the Class I positive electrode material and the Class II positive electrode material, and can be 500, 1000, 1500, 2000, 2500, 3000, or any value between 500 and 3000 ppm.

[0083] The specific surface area of ​​the lithium cobalt oxide positive electrode material is 0.14 to 0.24 m 2 / g, can be 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, or 0.14-0.24m 2 / g; tap density is 2.8~3.2g / cm 3 , can be 2.8, 2.9, 3.0, 3.1, 3.2, or 2.8-3.2 g / cm 3 Any value between 4.04 and 4.18 g / cm 3 , can be 4.04, 4.05, 4.06, 4.08, 4.1, 4.12, 4.14, 4.15, 4.16, 4.18, or 4.04-4.18 g / cm 3 Any value in between.

[0084] The present invention also provides a method for preparing a lithium cobalt oxide positive electrode material, comprising the following steps:

[0085] The type I positive electrode material, the type II positive electrode material and the coating material are mixed and calcined to obtain a lithium cobalt oxide positive electrode material.

[0086] Among them, the type I positive electrode material, type II positive electrode material and coating material are as described above and will not be elaborated here.

[0087] The calcination is as follows: the temperature is raised to 700°C to 900°C at a heating rate of 2 to 4°C / min, and the temperature is kept at this temperature for 5 to 8 hours; the heating rate can be 2, 2.5, 3, 3.5, 4, or any value between 2 and 4°C / min. The calcination temperature can be 700, 750, 800, 750, 900, or any value between 700°C and 900°C, and the holding time can be 5, 6, 7, 8, or any value between 5 and 8 hours. The calcination atmosphere is air, oxygen or nitrogen.

[0088] In the present invention, the equipment used for calcining may be a muffle furnace, a tunnel furnace, a roller kiln, a tubular furnace or other types of calcining equipment, which is not limited here.

[0089] After calcination, the material is crushed to obtain lithium cobalt oxide positive electrode material.

[0090] The present invention also provides a positive electrode plate, comprising the above-mentioned lithium cobalt oxide positive electrode material. The positive electrode plate made by using the above-mentioned lithium ion battery positive electrode material has excellent capacity and good cycle stability under high voltage.

[0091] The present invention also provides a lithium ion battery, comprising the above-mentioned positive electrode sheet. The lithium ion battery has the advantages of excellent conductivity, high discharge capacity and good cycle retention rate.

[0092] The lithium cobalt oxide material with high compaction density provided by the present invention is prepared into a finished product with a large number of medium-sized particles by using a precursor material with a wide particle size distribution and a precursor material with a conventional particle size distribution, so that the particles can be better distributed, thereby achieving the purpose of improving energy density and cycle life under high voltage.

[0093] In order to further understand the present invention, the lithium cobalt oxide positive electrode material and its preparation method, positive electrode sheet, and battery provided by the present invention are described below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0094] Embodiment 1:

[0095] (1) 3 kg Co3O4 (D50 = 16.5 μm, Ti content of 8000 ppm, diameter distance of 0.9, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.55 kg Li2CO3 and 17.49 g MgO were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.07:1, and the MgO content was 1000 ppm. The mixture was heated to 600°C at a heating rate of 4°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1055°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled naturally to room temperature and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅰ) is 18.5 μm, and a type I positive electrode material is obtained;

[0096] (2) 3 kg Co3O4 (D50 = 4.0 μm, Ti content of 7000 ppm, diameter distance of 0.8, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.3 kg Li2CO3 and 6.9 g Y2O3 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.05:1, the Y2O3 content was 1500 ppm, and heated to 600°C at a heating rate of 4°C / min in the first stage, and kept at this temperature for 4 h. In the second stage, the temperature was heated to 995°C at a heating rate of 3°C / min, and kept at this temperature for 8 h. The mixture was cooled naturally to room temperature and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅱ) is 4.6 μm, and a type II positive electrode material is obtained;

[0097] (3) 1.2 kg of type I positive electrode material, 0.3 kg of type II positive electrode material, 70 g of nano cobalt carbonate and 0.8 g of ZrO2 were mixed in a high-speed mixer at 1100 r / min for 45 min, wherein the content of ZrO2 was 500 ppm, and heated to 900°C at a heating rate of 2°C / min, kept at that temperature for 6 h, and naturally cooled to room temperature to obtain a precursor-improved lithium cobalt oxide material;

[0098] Embodiment 2:

[0099] (1) 3 kg Co3O4 (D50 = 16.5 μm, Ti content of 7000 ppm, diameter distance of 0.9, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.55 kg Li2CO3, 2.8 g Al2O3 and 18.5 g NbO were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.07:1, the Al2O3 content was 400 ppm, and the NbO content was 1000 ppm. The mixture was heated to 600°C at a heating rate of 5°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1065°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅰ)is 19.5 μm, and a type I positive electrode material is obtained;

[0100] (2) 3 kg Co3O4 (D50 = 4.0 μm, W content of 10000 ppm, diameter distance of 0.8, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.35 kg Li2CO3 and 3.5 g WO3 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.05:1, the WO3 content was 700 ppm, and heated to 600°C at a heating rate of 5°C / min in the first stage and kept at this temperature for 4 h, and heated to 1005°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h, and then cooled naturally to room temperature and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅱ) is 5.0 μm, and a type II positive electrode material is obtained;

[0101] (3) 1.2 kg of Class I positive electrode material, 0.3 kg of Class II positive electrode material, 70 g of nano-cobalt carbonate and 0.88 g of TiO2 were mixed in a high-speed mixer at 1100 r / min for 45 min, wherein the TiO2 content was 700 ppm, and heated to 800°C at a heating rate of 3°C / min, kept at that temperature for 6 h, and naturally cooled to room temperature to obtain a precursor-improved lithium cobalt oxide material.

[0102] Embodiment 3:

[0103] (1) 3 kg Co3O4 (D50 = 16.5 μm, Al content of 8000 ppm, diameter distance of 0.9, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.55 kg Li2CO3 and 3.5 g In2O3 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.07:1, and the In2O3 content was 1000 ppm. The mixture was heated to 600°C at a heating rate of 6°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1075°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅰ) is 18.9 μm, and a type I positive electrode material is obtained;

[0104] (2) 3 kg Co3O4 (D50 = 4.0 μm, Zr content of 8000 ppm, diameter distance of 0.8, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.35 kg Li2CO3 and 1.5 g GeO2 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.05:1 and the GeO2 content was 700 ppm. The mixture was heated to 600°C at a heating rate of 6°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1000°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅱ) is 4.5 μm, and a type II positive electrode material is obtained;

[0105] (3) 1.2 kg of Class I positive electrode material, 0.3 kg of Class II positive electrode material, 70 g of nano-cobalt carbonate and 0.5 g of La2O3 were mixed in a high-speed mixer at 1100 r / min for 45 min, wherein the content of La2O3 was 500 ppm, and heated to 700°C at a heating rate of 3°C / min, kept at that temperature for 6 h, and naturally cooled to room temperature to obtain a precursor-improved lithium cobalt oxide material.

[0106] Embodiment 4:

[0107] (1) 3 kg Co3O4 (D50 = 16.5 μm, Al content of 8000 ppm, diameter distance of 0.9, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.55 kg Li2CO3 and 1.5 g Nb2O5 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.07:1 and the Nb2O5 content was 1000 ppm. The mixture was heated to 600°C at a heating rate of 6°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1075°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅰ) is 18.9 μm, and a type I positive electrode material is obtained;

[0108] (2) 3 kg Co3O4 (D50 = 4.0 μm, Zr content of 8000 ppm, diameter distance of 0.8, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.35 kg Li2CO3 and 1.5 g GeO2 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.05:1 and the GeO2 content was 700 ppm. The mixture was heated to 600°C at a heating rate of 6°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1000°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅱ) is 4.5 μm, and a type II positive electrode material is obtained;

[0109] (3) 1.2 kg of Class I positive electrode material, 0.3 kg of Class II positive electrode material, 70 g of nano-cobalt carbonate and 0.5 g of La2O3 were mixed in a high-speed mixer at 1100 r / min for 45 min, wherein the content of La2O3 was 500 ppm, and heated to 700°C at a heating rate of 3°C / min, kept at that temperature for 6 h, and naturally cooled to room temperature to obtain a precursor-improved lithium cobalt oxide material.

[0110] Embodiment 5:

[0111] (1) 3 kg Co3O4 (D50 = 16.5 μm, Al content of 8000 ppm, diameter distance of 0.9, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.55 kg Li2CO3 and 1.5 g Nb2O5 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.07:1 and the Nb2O5 content was 1000 ppm. The mixture was heated to 600°C at a heating rate of 6°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1075°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅰ) is 18.9 μm, and a type I positive electrode material is obtained;

[0112] (2) 3 kg Co3O4 (D50 = 4.0 μm, Ni content of 7000 ppm, diameter distance of 0.8, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.35 kg Li2CO3 and 1.5 g GeO2 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.05:1 and the GeO2 content was 700 ppm. The mixture was heated to 600°C at a heating rate of 6°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1000°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅱ) is 4.5 μm, and a type II positive electrode material is obtained;

[0113] (3) 1.2 kg of Class I positive electrode material, 0.3 kg of Class II positive electrode material, 70 g of nano-cobalt carbonate and 0.5 g of La2O3 were mixed in a high-speed mixer at 1100 r / min for 45 min, wherein the content of La2O3 was 500 ppm, and heated to 700°C at a heating rate of 3°C / min, kept at that temperature for 6 h, and naturally cooled to room temperature to obtain a precursor-improved lithium cobalt oxide material.

[0114] Embodiment 6:

[0115] (1) 3 kg Co3O4 (D50 = 16.5 μm, Mg content of 8000 ppm, diameter distance of 0.9, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.55 kg Li2CO3 and 1.5 g Nb2O5 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.07:1 and the Nb2O5 content was 1000 ppm. The mixture was heated to 600°C at a heating rate of 6°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1075°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅰ) is 18.9 μm, and a type I positive electrode material is obtained;

[0116] (2) 3 kg Co3O4 (D50 = 4.0 μm, Mg content of 8000 ppm, diameter distance of 0.8, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.35 kg Li2CO3 and 1.5 g GeO2 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.05:1, and the GeO2 content was 700 ppm. The mixture was heated to 600°C at a heating rate of 6°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1000°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅱ) is 4.5 μm, and a type II positive electrode material is obtained;

[0117] (3) 1.2 kg of Class I positive electrode material, 0.3 kg of Class II positive electrode material, 70 g of nano-cobalt carbonate and 0.5 g of La2O3 were mixed in a high-speed mixer at 1100 r / min for 45 min, wherein the content of La2O3 was 500 ppm, and heated to 700°C at a heating rate of 3°C / min, kept at that temperature for 6 h, and naturally cooled to room temperature to obtain a precursor-improved lithium cobalt oxide material.

[0118] Comparative Example 1:

[0119] (1) 3 kg Co3O4 (D50 = 16.5 μm, Ti content of 8000 ppm, diameter distance of 0.3, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.55 kg Li2CO3 and 17.49 g MgO were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.07:1, and the MgO content was 1000 ppm. The mixture was heated to 600°C at a heating rate of 4°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1055°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅰ) is 18.6 μm, and a type I positive electrode material is obtained;

[0120] (2) 3 kg Co3O4 (D50 = 4.0 μm, Ti content of 7000 ppm, diameter distance of 0.8, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.3 kg Li2CO3 and 6.9 g Y2O3 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.05:1, the Y2O3 content was 1500 ppm, and heated to 600°C at a heating rate of 4°C / min in the first stage, and kept at this temperature for 4 h. In the second stage, the temperature was heated to 995°C at a heating rate of 3°C / min, and kept at this temperature for 8 h. The mixture was cooled naturally to room temperature and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅱ) is 4.0 μm, and a type II positive electrode material is obtained;

[0121] (3) 1.2 kg of Class I positive electrode material, 0.3 kg of Class II positive electrode material, 70 g of nano-cobalt carbonate and 0.8 g of ZrO2 were mixed in a high-speed mixer at 1100 r / min for 45 min, wherein the ZrO2 content was 500 ppm, and heated to 900°C at a heating rate of 2°C / min, kept at that temperature for 6 h, and naturally cooled to room temperature to obtain lithium cobalt oxide material.

[0122] Comparative Example 2:

[0123] (1) 3 kg Co3O4 (D50 = 16.5 μm, Ti content of 7000 ppm, diameter distance of 0.3, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.55 kg Li2CO3, 2.8 g Al2O3 and 18.5 g NbO were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.07:1, the Al2O3 content was 400 ppm, and the NbO content was 1000 ppm. The mixture was heated to 600°C at a heating rate of 5°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1065°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅰ) is 18.5 μm, and a type I positive electrode material is obtained;

[0124] (2) 3 kg Co3O4 (D50 = 4.0 μm, W content of 10000 ppm, diameter distance of 0.8, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.35 kg Li2CO3 and 3.5 g WO3 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.05:1, the WO3 content was 700 ppm, and heated to 600°C at a heating rate of 5°C / min in the first stage and kept at this temperature for 4 h, and heated to 1005°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h, and then cooled naturally to room temperature and crushed to a median particle size D of the lithium cobalt oxide powder.50(Ⅱ) is 5.0 μm, and a type II positive electrode material is obtained;

[0125] (3) 1.2 kg of Class I positive electrode material, 0.3 kg of Class II positive electrode material, 70 g of nano-cobalt carbonate and 0.55 g of TiO2 were mixed in a high-speed mixer at 1100 r / min for 45 min, wherein the TiO2 content was 700 ppm, and heated to 800°C at a heating rate of 3°C / min, kept at that temperature for 6 h, and naturally cooled to room temperature to obtain lithium cobalt oxide material without classification.

[0126] Comparative Example 3:

[0127] 3kgCo3O4 (D50=16.5μm, Al content of 8000ppm, diameter distance of 0.3, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.55kgLi2CO3 and 3.5gIn2O3 were mixed in a high-speed mixer at 900r / min for 45min, wherein the lithium-cobalt ratio was 1.07:1, the In2O3 content was 1000ppm, and heated to 600℃ at a heating rate of 6℃ / min in the first stage, and kept warm for 4h, and heated to 1075℃ at a heating rate of 3℃ / min in the second stage, and kept warm for 8h, and cooled naturally to room temperature, and crushed to a median particle size D of lithium cobalt oxide powder. 50(Ⅰ) is 18.9 μm, and a type I positive electrode material is obtained;

[0128] (2) 3 kg Co3O4 (D50 = 4.0 μm, Zr content of 8000 ppm, diameter distance of 0.8, purchased from Zhejiang Huayou Cobalt Co., Ltd.), 1.35 kg Li2CO3 and 1.5 g GeO2 were mixed in a high-speed mixer at 900 r / min for 45 min, wherein the lithium-cobalt ratio was 1.05:1 and the GeO2 content was 700 ppm. The mixture was heated to 600°C at a heating rate of 6°C / min in the first stage and kept at this temperature for 4 h. The mixture was heated to 1000°C at a heating rate of 3°C / min in the second stage and kept at this temperature for 8 h. The mixture was cooled to room temperature naturally and crushed to a median particle size D of the lithium cobalt oxide powder. 50(Ⅱ) is 4.8 μm, and a type II positive electrode material is obtained;

[0129] (3) 1.2 kg of Class I positive electrode material, 0.3 kg of Class II positive electrode material, 70 g of nano-cobalt carbonate and 0.5 g of La2O3 were mixed in a high-speed mixer at 1100 r / min for 45 min, wherein the content of La2O3 was 500 ppm, and heated to 700°C at a heating rate of 3°C / min, kept at that temperature for 6 h, and naturally cooled to room temperature to obtain lithium cobalt oxide material without classification.

[0130] Test Case

[0131] 1. The present invention obtains two precursor particle morphology images by SEM technology ( Figure 1-2 ), the conventional particle size distribution precursor has a uniform particle size, while the wide particle size distribution precursor has different particle sizes; the present invention uses laser light scattering technology to statistically analyze the particle size distribution of the two precursor particles ( Figure 3 ), the wide particle size distribution precursor has a wider distribution, indicating that the particles have different particle sizes, which corresponds to the SEM results.

[0132] 2. The particle size distribution of the type I positive electrode material in Example 1 and Comparative Example 1 was tested, and the particle size distribution of the type I positive electrode material in Example 1 and Comparative Example 1 was obtained as shown in the figure: Figure 4 As shown, in Figure 4 The precursor with a wide particle size distribution is inherited in the Type I cathode material, that is, the particle size volume density in the Type I cathode material is significantly increased.

[0133] 3. The finished products in Examples 1 to 6 and Comparative Example 1 were tested for particle size distribution, and the particle size distribution diagrams of the finished products in Examples 1 to 6 and Comparative Example 1 were obtained as shown in Figure 5 As shown, in Figure 5 In the example, the number of medium-sized particles increases after the type I positive electrode material prepared by the wide particle size distribution precursor is prepared into the finished product, indicating that the advantages of the wide particle size precursor can be sustained into the finished product; in addition, compared with the conventional finished product, the connection between the large and small particles is smoother, and the distribution of the large and small particles is more continuous. The finished products in Example 1 and Comparative Example 1 were tested by SEM, and the SEM images of the finished products in Example 1 and Comparative Example 1 are as follows: Figure 6 As shown, in Figure 6 In Example 1 (left), the number of particles with medium particle size (4.5-10 μm) increased significantly, which is consistent with Figure 5 Be consistent.

[0134] 4. The compaction density test of the powder materials in Example 1 and Comparative Example 1 was carried out respectively. The test results are as follows: Figure 7 As shown. Figure 7 It can be seen that the precursor with wide particle size distribution can effectively improve the compaction density.

[0135] The performance test results of the positive electrode materials of the embodiment and the comparative example are shown in Table 1

[0136] Table 1

[0137] <![CDATA[Specific surface area / m 2 / g]]> <![CDATA[Tap density / g / cm 3 > <![CDATA[Compaction density / g / cm 3 > Example 1 0.183 2.80 4.09 Example 2 0.180 2.83 4.08 Example 3 0.181 2.85 4.11 Example 4 0.179 2.81 4.10 Example 5 0.181 2.84 4.12 Example 6 0.182 2.81 4.08 Comparative Example 1 0.169 2.70 3.93 Comparative Example 2 0.166 2.75 3.89 Comparative Example 3 0.168 2.85 3.91

[0138] Electrical performance test

[0139] (1) Preparation of positive electrode sheets for lithium-ion half-cells: The lithium cobalt oxide positive electrode materials obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were uniformly mixed with conductive agent acetylene black (Super P) and polyvinylidene fluoride PVDF in a mass ratio of 8:1:1, and the mixture was adjusted into a slurry with N-methyl-pyrrolidone (NMP), and then evenly applied on an aluminum foil. After vacuum drying, the pressed sheets were taken out and cut into positive electrode sheets of a desired size;

[0140] (2) Preparation of lithium-ion half-cell: The lithium-ion battery is assembled from the above-mentioned positive electrode sheet, lithium negative electrode, separator between the positive and negative electrodes, and electrolyte. The assembled battery is used for capacity testing and cycle testing.

[0141] The first charge and discharge test under 3.0-4.60V voltage cycle is shown in Figure 8 ;

[0142] 45℃, 3.0-4.60V voltage cycle cycle retention test see Fig. 9 ;

[0143] The comprehensive electrical properties are shown in Table 2.

[0144] Table 2

[0145]

[0146]

[0147] It can be seen from the performance test data that the charge and discharge specific capacity of Examples 1 to 6 and Comparative Examples 1 to 3 at 0.1C is increased by 4 mAh / g and maintained in a good state; the cycle retention rate of Examples 1 to 6 and Comparative Examples 1 to 3 is maintained at a good level after 50 charge and discharge cycles under high temperature and high pressure, indicating that the precursor of the present invention improves the lithium cobalt oxide material and has the technical effect of significantly improving the energy density and high-voltage stability of the lithium cobalt oxide material.

[0148] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A lithium cobalt oxide positive electrode material, characterized in that: Including Class I positive electrode materials and Class II positive electrode materials; The chemical formula of the type I positive electrode material is Li u Co 1-x A x O2; wherein 1.05<u≤1.07, 0≤x<1, A comprises at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, zirconium, niobium, indium, fluorine, chlorine, and sulfur; The chemical formula of the type II positive electrode material is Li v Co 1-y M y O2; wherein 1.05<v≤1.07, 0≤y<1, and M comprises at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, strontium, germanium, niobium, indium, zirconium, fluorine, chlorine, and sulfur; The median particle size D of the type I positive electrode material 50(Ⅰ) The median particle size D of the type II positive electrode material is 16.5 μm to 20.5 μm. 50(Ⅱ) 4.0μm~6.5μm; The mass ratio of the type I positive electrode material to the type II positive electrode material is 3 to 5:1; The compaction density of the lithium cobalt oxide positive electrode material is 4.04-4.18 g / cm 3 .

2. The positive electrode material according to claim 1, characterized in that The type I positive electrode material is prepared from a precursor material having a wide particle size distribution; The type II positive electrode material is prepared from a precursor material having a conventional particle size distribution; The wide particle size distribution precursor material has a diameter distance of 0.80 to 1.00 and a median particle size of 15 to 18 μm; The conventional particle size distribution of the precursor material has a diameter distance of 0.2 to 0.3 μm and a median particle size of 2.5 to 6 μm.

3. The positive electrode material according to claim 2, characterized in that The wide particle size distribution precursor material is a doped cobalt-containing precursor material, the cobalt-containing precursor is selected from one or more of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt carbonate, cobalt oxalate and cobalt oxyhydroxide, the doping element is one or more of aluminum, magnesium, nickel, manganese, titanium and zirconium, and the doping amount of the doping element is 6000-9000ppm; The conventional particle size distribution precursor material is a doped cobalt-containing precursor material, the cobalt-containing precursor is selected from one or more of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt carbonate, cobalt oxalate and cobalt oxyhydroxy, the doping element is one or more of aluminum, magnesium, nickel, manganese, titanium and zirconium, and the doping amount of the doping element is 6000 to 11000 ppm.

4. The positive electrode material according to claim 1, characterized in that The raw materials for preparing the lithium cobalt oxide positive electrode material also include a coating material, which includes a cobalt source compound and a compound containing a coating element, wherein the coating element is at least one of magnesium, tungsten, titanium, yttrium, aluminum, nickel, manganese, strontium, germanium, niobium, indium, zirconium, lanthanum and halogen elements; the cobalt source compound is selected from one or more of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, nano cobalt carbonate and cobalt oxyhydroxyl; The cobalt source compound accounts for 0.25% to 0.75% of the total mass of the type I positive electrode material and the type II positive electrode material; The compound containing the coating element accounts for 500 to 3000 ppm of the total mass of the type I positive electrode material and the type II positive electrode material.

5. The positive electrode material according to claim 1, characterized in that The specific surface area of ​​the lithium cobalt oxide positive electrode material is 0.14-0.24m 2 / g, tap density is 2.8-3.2g / cm 3 .

6. A method for preparing a lithium cobalt oxide positive electrode material, characterized in that: The following steps are involved: The type I positive electrode material, the type II positive electrode material and the coating material are mixed and calcined to obtain a lithium cobalt oxide positive electrode material.

7. The preparation method according to claim 6, characterized in that: The calcination is as follows: raising the temperature to 700°C to 900°C at a heating rate of 2 to 4°C / min, and keeping the temperature for 5 to 8 hours; The calcination atmosphere is air, oxygen or nitrogen.

8. The preparation method according to claim 6, characterized in that: The preparation method of the Class I positive electrode material comprises: The wide particle size distribution precursor, the lithium source and the compound containing the A element are uniformly mixed, calcined and crushed to obtain a type I positive electrode material; The preparation method of the type II positive electrode material comprises: The conventional particle size distribution precursor, the lithium source and the compound containing the M element are uniformly mixed, calcined and crushed to obtain the type II positive electrode material; Preferably, the lithium source used to prepare the type I positive electrode material and the type II positive electrode material is independently selected from one or more of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide and lithium fluoride; Preferably, the calcination in the process of preparing the Class I positive electrode material comprises two stages, the first stage is to increase the temperature to 600°C to 800°C at a heating rate of 3 to 8°C / min and keep it warm for 2 to 4 hours, and the second stage is to increase the temperature to 1050°C to 1100°C at a heating rate of 1 to 3°C / min and keep it warm for 5 to 8 hours; The calcination process in the preparation of the Class II positive electrode material includes two stages. The first stage is to increase the temperature to 600°C to 800°C at a heating rate of 3 to 8°C / min and keep it warm for 2 to 4 hours. The second stage is to increase the temperature to 980°C to 1015°C at a heating rate of 1 to 3°C / min and keep it warm for 5 to 8 hours.

9. A positive electrode sheet, characterized in that: The invention comprises the lithium cobalt oxide positive electrode material as claimed in any one of claims 1 to 5.

10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.